Best Practice: Integrated Marketing Communications - Schultz, Don; Macdonald, Emma K.; Baines, Paul R. (Cranfield University, 2012)
Integrated marketing communications can substantially improve target audience reception, message resonance, and positive behavioural response but, to reach its true potential, the process requires a strong focus on data integration/customer insight.
Keywords: integrated marketing communications, IMC, outbound communications, advertising, media consumption, real time experience tracking